Competing Visions of Mission and Unity among Japanese Protestants and Missionaries in Japan (1859–1912). (10th November 2021) - Hastings, Thomas John
Abstract: After a brief clarification of terms, this article focuses on the early history of the minority Protestant movement in Japan around the turn of the 20th century, examining rival perspectives on mission and unity among certain Japanese church leaders and Western missionaries. The sudden rise of Japan as the regional political power in Northeast Asia strongly influenced both constituencies, albeit in differing ways. While Protestant missionaries imagined Japanese Christians as future agents in their strategy for world evangelization, Japanese Protestant leaders were more modest, focusing their energies on the development of an independent national church. They did hope that their theological "liberation" from British, Dutch, and German confessional traditions would inspire similar theological developments in "younger churches" elsewhere. In light of the Japanese case, the author turns to John 17 for a "post‐instrumentalist" proposal for Christian unity and mission grounded in the inner life of God and wonders if such a perspective may be better attuned to the polycentric ecumenism of this new era of World Christianity.